Antagonistic pleiotropic effects of nitric oxide in the pathophysiology of Parkinson's disease. (September 2015) - Tripathy, D.; Chakraborty, J.; Mohanakumar, K. P.
Abstract Sporadic Parkinson's disease (PD) is a geriatric disorder with unknown etiology, specifically affecting the nigrostriatal dopaminergic (DA-ergic) pathway of the brain. Amongst several contributing factors, nitric oxide (NO) is considered to inflict injury to DA-ergic neurons, and to influence PD progression. Supportive evidence for this comes from animal models of PD, where inhibitors of NO synthase (NOS) are found to protect against DA-ergic neuronal death, and NOS-deficient mice are found to be resistant to PD-producing neurotoxins. Presence of nitrated proteins and upregulated levels of NOS in human postmortem PD brain samples have rendered further support to this contention. While NO from neuronal NOS contributes to neurodegeneration in PD, NO produced by inducible NOS from proliferating microglia as inflammatory responses to neuronal insults are suggested to mediate the disease progression. Another view that NO in small doses serves as a neuroprotective agent in the brain is also discussed, in light of experimental evidence available in vitro and in vivo. This view is based on the argument that NO could form harmless nitrites and nitrates on reaction with endogenously produced reactive oxygen species (ROS) within the cells. This review essentially discusses the possibilities of considering NO as a secondary response of DA-ergic cell death, while oxidative stress is the primary cause. Once neurons undergo death processes following uncontrolled oxidative insult, the resulting gliosis-mediated NO accelerates the events as a secondary mediator. Since the time of initiation of DA-ergic cell death cannot be predicted, NO could be an ideal molecular target to halt the disease progression.